The Unholy Fire and Theological Construction: Reflection for Today's Services: Api Asing dan Konstruksi Teologi: Reflektif Bagi Pelayanan Masa Kini - Yonatan Alex Arifianto (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2022)
Today's life has been infiltrated by many models of service based on the wrong spirit and motivation among the church, God's servants and individual believers. The basis of service that is not in accordance with God's will is illustrated as an unauthorized fire in the story of Nadab and Abihu. This research intends to convey the meaning of unauthorized fire in today's service life. The research is also provide an understanding of  the action that  believers should do so that the mistakes of Nadab and Abihu are not repeated in today's service life. Qualitative approach method, with literature study and hermeneutic technique of biblical texts. The conclusion is that the ministry of believers today needs to reflect on the story of Nadab and Abihu to then evaluate the service, what fire is currently used as a spirit of service, a foreign fire or God's fire. The elements contained in the use of God's fire to be absolute to be applied in the ministry of believers include; First, holiness. Second, obedience. Third, humility . Fourth, responsibility.